Research on dynamic migration of virtual machine based on security level - Shuo ZHAO; Xin-sheng JI; Yu-xing MAO; Guo-zhen CHENG; Hong-chao HU (Tongxin xuebao)
Side-channel attacks were the main ways of multi-tenant information leakage in the cloud computing and data center environments.The existing defense approaches based on dynamic migration of virtual machine have long convergence time of migration algorithm and high migration cost.Hence,a dynamic migration of virtual machine based on security level was proposed.Firstly,security level classification of virtual machines was used to reduce the number of migrating virtual machines.Then the corresponding virtual machines embedding strategy was used to reduce the frequency of virtual machines migration.Simulation experiments demonstrate that the proposed approach can reduce convergence time of migration algorithm and migration cost.